KATA GABUNG BAHASA JEPANG - Lina Rosliana (KIRYOKU, 2017)
The word in Japanese linguistics is commonly referred to as tango 単 語 or go 語. Japanese words can be grouped according to their history, class, and process of formation. This research will discuss the word based on the process of its formation. The process of word formation is the main focus in the branch of morphological linguistics, which in turn spawned several theories. This study uses the theory of Akimoto which divides the word into 2 types, namely single word, and the word join. The word join includes compound words, word reduplication, and derivation. This study uses literature study method using references from various linguistic books of Japanese language.